Позитивні зобов’язання держави щодо забезпечення реалізації прав людини - Горпинюк, Оксана (Видавництво Львівської політехніки, 2018)
The types of positive obligations of the state in the observance of right on respect of private and domestic life are examined in the article. Principles of positive obligation of the states are determine. The algorithm of considerations of the European court of human rights observance of positive obligations of the state in the relations of right on respect of private life are certain.
Keywords: the practice of European court of human rights; positive obligations of the state; the right on respect of private life